(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Disaster response and recovery are very necessary in disaster management. Decision-support systems used in disaster management must have to deal with the complexity and uncertainty related in these kinds of situations. Operational conditions, precedence conditions, resource availability make the resource allocation more difficult and harder. Failure to assign proper humans and proper strategies may harm the reputation of the organization. Therefore, this paper proposes a resource allocation system for such post disaster situations